A win‐win strategy for an integrated vendor‐buyer deteriorating inventory system - Yang, P. C.; Wee, H. M. (Mathematical Modelling and Analysis, 2006)
An integrated approach considering the view of both the buyer and the vendor is discussed in this study. It can be shown numerically that the integrated approach results in an impressive cost reduction when compared with an independent decision approach by the buyer. Although the integrated total cost decreases, the buyer's cost increases due to larger orders. To entice the buyer to accept larger order quantity, a permissible delay in payment is offered by the vendor to the buyer. A negotiation factor is also incorporated to share the benefits.First Published Online: 14 Oct 2010